Mass Balance of C, Nutrients, and Mineralization of Nitrogen during Anaerobic Co-Digestion of Rice Straw with Cow Manure - Furqan Muhayodin (MDPI AG, 2021)
Anaerobic co-digestion technology (AcoD) can be used to process rice straw (RS) and cow manure (CoM) to produce energy and a digestate rich in nutrients, while the improper disposal of RS and CoM causes environmental problems. The overall effectiveness of the anaerobic digestion technology can be improved by utilizing the nutrients available in the digestate. It is also a way to reduce the usage of mineral fertilizer by recycling the nutrients available in the digestate. The co-digestion of RS with CoM was performed in a newly developed digester (F1) and in a mesophilic digester (F2) used as a reference. The mass balance of C, macronutrients (N, P, K, Ca, Mg, and S), and their distribution into a liquid digestate (LD) and a solid digestate (SD) was investigated in both digesters. The mass balance was used to evaluate the carbon available in the biogas and in the digestate. It was also used to investigate the recovery potential of the macronutrients after the AD process. Moreover, the assessment of the resulting digestate was carried out to suggest its potential use in agriculture. The amount of C measured in the biogas was the same in both digesters (41.0% and 38.0% of the initial C). Moreover, the conversion efficiency of C from the substrate into methane was 23.4% for F1 and 21.0% for F2. The Ca, Mg, K, and P were conserved in the digestate because their recovery rates (RR) were close to 100%. However, a relatively low RR was observed for N (84.1% in F1 and 86.8% in F2) and S (87.1% in F1 and 86.5% in F2) in both the digesters. After separation n of the SD, from 79.1 to 83.4% (in F1) and 75.0 to 82.4% (in F2) of the final nutrients were available in the LD. The assessment of the SD suggested its use in agriculture not only for soil amendment but also as a K-providing organic fertilizer.